2011
DOI: 10.1007/s00520-011-1168-y
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in short-term and long-term all-cause mortality among Korean cancer patients with and without preexisting disabilities: a nationwide retrospective cohort study

Abstract: This study raises concerns with regard to disability-related disparities in cancer outcome among long-term cancer survivors. Further attention and effective collaborative efforts are required for improvement of survival and quality of care for long-term cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The studies showed that cancer treatment was suboptimal for PwD in many ways, and in particular that they had a lower likelihood of undergoing guideline-consistent surgery when indicated [ 22 , 40 , 42 , 54 , 58 , 61 , 63 , 65 ]. Several studies showed that when PwD were correctly treated with guideline-consistent surgery, their mortality was similar or only slightly higher than controls [ 55 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies showed that cancer treatment was suboptimal for PwD in many ways, and in particular that they had a lower likelihood of undergoing guideline-consistent surgery when indicated [ 22 , 40 , 42 , 54 , 58 , 61 , 63 , 65 ]. Several studies showed that when PwD were correctly treated with guideline-consistent surgery, their mortality was similar or only slightly higher than controls [ 55 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine other studies (29%, n = 9) considered all disability in general or grouped into subcategories (e.g. physical/communication/mental/internal organ/others) [19,22,23,55,[58][59][60][61][62]. Few studies differentiated by severity of impairment [19,22,60,62,63].…”
Section: Types Of Disabilitiesmentioning
confidence: 99%
“…A study of the Dutch adult population also found that cancer-related mortality was more common in individuals with intellectual disability [ 10 ]. Likewise, a previous study in Korea reported that cancer patients with disabilities had higher long-term all-cause mortality, and that such propensities also tended to persist in 5-year cancer survivors, suggesting the need for further collaborative efforts to improve the survival of cancer patients and survivors [ 23 ]. Another study similarly demonstrated a higher risk of overall mortality in cervical cancer patients with disabilities and concluded that social support and policies were needed to improve such disparities [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Korean National Health Information Database used in this study provides a unique opportunity to analyze population features on a large scale. The Korean National Health Insurance Service covers all Korean citizens, and the random sample is designed to be nationally representative [61]. Its universal healthcare system with income-based premiums allows people to seek healthcare with less financial burden.…”
Section: Discussionmentioning
confidence: 99%